Corruption prevention practices and tax avoidance: The moderating effect of corporate board characteristics - Mohamed Elmagrhi (Journal of International Accounting, Auditing and Taxation, 2024)
This paper examines the impact of corruption prevention practices on tax avoidance from a neo-institutional theoretical perspective. Our study also contributes to the existing corruption and tax literature by considering the moderating effect of corporate board characteristics on the association between corruption prevention practices and tax avoidance. Based on a sample of FTSE 350 UK listed firms, our findings illustrate that a firm’s commitment to good anti-corruption practices is linked with lower tax avoidance. Furthermore, corporate board characteristics complement anti-corruption practices in minimising corporate tax avoidance. Our findings provide useful evidence to governments, regulators and other stakeholders who aim to determine best business practices that could help in reducing risk of corporate tax avoidance. In general, our findings are robust to alternative measures of tax avoidance and different types of multivariate regression methods, namely ordinary least squares, two-stage least squares and Tobit regression techniques to analyse collected data.